A monomeric organolithium compound containing a free pyramidal carbanion in solution and in the solid state. - Breher, F; Grunenberg, J; Lawrence, S; Mountford, P; Rüegger, H (2004)
A suitable bridle, created by intramolecular chelation of the Li cation, and lack of π delocalization, yielded the first monomeric lithium organyl compound containing an unassociated tetrahedral carbanionic center (see picture). The zwitterionic structure found in the solid state is preserved in solution. Only weak electrostatic Li+⋯C- interactions are apparent; there is no Li-C contact and therefore no "classical" aggregation.